Children's brain activations while viewing televised violence revealed by fMRI - Murray, John P.; Liotti, Mario; Ingmundson, Paul T.; Mayberg, Helen S.; Pu, Yonglin; Zamarripa, Frank; Liu, Yijun; Waldorff, Marty G.; Gao, Jia-Hong; Fox, Peter T. (My University, 2008)
Though social and behavioral effects of TV violence have been studied extensively, the brain systems involved in TV violence viewing in children are, at present, not known. In this study, 8 children viewed televised violent and nonviolent video sequences while brain activity was measured with functional magnetic resonance imaging. Both violent and nonviolent viewing activated regions involved in visual motion, visual object and scenes, and auditory listening. However, viewing TV violence selectively recruited a network of right hemisphere regions including precuneus, posterior cingulate, amygdala, inferior parietal, and prefrontal and premotor cortex. Bilateral activations were apparent in hippocampus, parahippo-campus, and pulvinar. TV violence viewing transiently recruits a network of brain regions involved in the regulation of emotion, arousal and attention, episodic memory encoding and retrieval, and motor programming. This pattern of brain activations may explain the behavioral effects observed in many studies, especially the finding that children who are frequent viewers of TV violence are more likely to behave aggressively. Such extensive viewing may result in a large number of aggressive scripts stored in long-term memory in the posterior cingulate, which facilitates rapid recall of aggressive scenes that serve as a guide for overt social behavior.
Keywords: Children; Media; Violence; Television; Brain; Neurological